AKUNTABILITAS, TRANSPARANSI DAN KINERJA UPK KECAMATAN PNPM MANDIRI PEDESAAN - Hari Susanto; Supranoto '; Hary Yuswadi (Universitas Riau, 2016)
Accountability, Transparency and Performance UPK PNPM Mandiri Rural District. This study aims to determine the effect of accountability and transparency on the performance of Activity Management Unit (UPK) District in PNPM Rural in Situbondo, either partially or simultaneously. Survey methods combined with a causal relationship approach applied in this study. The research instrument was a questionnaire, as the unit of analysis of the organization, the number of respondents overall total of 39 people, consisting of the entire board chairman, secretary and treasurer of a UPK 13 districts. The primary data of respondents’ perceptions of transparency and accountability to the organization’s performance is measured using questionnaires that have been tested level of validity (validity) and reliability (reliability). Multiple linear analysis was used to analyze the data. The results showed that accountability and transparency has a positive influence both simultaneously and partially on the performance of Activity Management Unit (UPK) District in PNPM Rural in Situbondo.